Beamforming Technology of LEO Satellite in Satellite-Terrestrial Integrated Network - Zhiyong LUO; Ning XIN; Shaohui SUN (天地一体化信息网络)
Because of the difference between satellite-ground link and ground propagation loss characteristics, the spectrum effi ciency index of satellite communication system is far lower than that of terrestrial cellular system in the same period.It is of utility to improve spectral effi ciency by realizing effi cient space division multiplexing with multi-beam antennas.The adaptive beamforming and doppler frequency off set compensation scheme in the LEO multi-beam satellite communication scenario was studied.Firstly, a low-complexity hybrid beamforming scheme was designed.Then, aim at the doppler frequency shifts were diff erent between beams due to their pitch angles, a doppler frequency off set pre-compensation scheme for multi-beam systems was proposed.Finally, the eff ectiveness of the algorithm was verifi ed by MATLAB simulation analysis.